2019
DOI: 10.4018/ijbir.2019010101
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Lack of Motivation in Aspirational Analytics Companies

Abstract: Establishing business intelligence analytics (BIA) in small- and medium-sized manufacturing enterprises is a pervasive problem. SME's - the majority of businesses - play an important role in creating jobs, but research is primarily focused on large corporations. The authors worked with small manufacturing companies at the aspirational capability level but found that their motivation to introduce BIA was low. They had many business challenges but perceived the obstacles (primarily cost and effort) as too great,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In particular, the director of C5 admitted that they do not use the data but fall back on conventional management ideas, citing that managing the childcare business is their second job. This finding is supported by Gudfinnsson et al. (2019), who found a limited motivation for SMEs to invest in any BI&A efforts.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, the director of C5 admitted that they do not use the data but fall back on conventional management ideas, citing that managing the childcare business is their second job. This finding is supported by Gudfinnsson et al. (2019), who found a limited motivation for SMEs to invest in any BI&A efforts.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, the director of C5 admitted that they do not use the data but fall back on conventional management ideas, citing that managing the childcare business is their second job. This finding is supported by Gudfinnsson et al (2019), who found a limited motivation for SMEs to invest in any BI&A efforts. In summary, the primary obstacles to novice BI&A leadership skills are the lack of knowledge and motivation in using available data for analysis and instead relying on heuristics and networking.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, both owners/managers (of SME2 and SME4) showed a preference for personal networks. This finding is supported by Gudfinnsson et al (2019), who found limited motivation for SMEs to invest in BI&A efforts. The owners/managers do not perceive value from the use of BI&A, although they have the TPS that generates data for BI&A.…”
Section: Novicementioning
confidence: 62%